Coastal Morphological Characteristics and Environmental Factors Causing Abrasion at Moilong Beach Based on GIS Analysis - Trisna Rahayu (Jurnal Serambi Engineering, 2026)
Coastal erosion is a major environmental problem in coastal areas resulting from the interaction of coastal morphology, oceanographic processes, and human activities. This study aims to identify the coastal morphological characteristics and environmental factors contributing to erosion at Moilong Beach, Banggai Regency, Central Sulawesi, using Geographic Information Systems (GIS) and field observations. The study integrated Landsat 8 imagery, the Indonesian National Digital Elevation Model (DEMNAS), geological, soil, bathymetric, watershed, land-use, and oceanographic datasets through spatial analysis. The results indicate that coastal erosion is primarily driven by the combination of a narrow sandy shoreline, unconsolidated Holocene alluvial deposits, gently sloping bathymetry that promotes longshore currents, reduced sediment supply from upstream watersheds, and land-use changes characterized by wetland conversion and mangrove degradation. Furthermore, the proximity of settlements and infrastructure to the shoreline significantly increases coastal vulnerability. The findings demonstrate that effective erosion mitigation requires an integrated coastal management approach involving mangrove restoration, sustainable watershed management, coastal spatial planning, and the implementation of both engineering-based and ecosystem-based protection measures to enhance long-term coastal resilience.